An RNA vaccine drives immunity in checkpoint-inhibitor-treated melanoma - Sahin, Ugur; Oehm, Petra; Derhovanessian, Evelyna; Jabulowsky, Robert A.; Vormehr, Mathias; Gold, Maike; Maurus, Daniel; Schwarck-Kokarakis, Doreen; Kuhn, Andreas N.; Omokoko, Tana; Kranz, Lena M.; Diken, Mustafa; et al. (Nature (London), 2020)
Treating patients who have cancer with vaccines that stimulate a targeted immune response is conceptually appealing, but cancer vaccine trials have not been successful in late-stage patients with treatment-refractory tumours 1 , 2 . We are testing melanoma FixVac (BNT111)—an intravenously administered liposomal RNA (RNA-LPX) vaccine, which targets four non-mutated, tumour-associated antigens that are prevalent in melanoma—in an ongoing, first-in-human, dose-escalation phase I trial in patients with advanced melanoma (Lipo-MERIT trial, ClinicalTrials.gov identifier NCT02410733). We report here data from an exploratory interim analysis that show that melanoma FixVac, alone or in combination with blockade of the checkpoint inhibitor PD1, mediates durable objective responses in checkpoint-inhibitor (CPI)-experienced patients with unresectable melanoma. Clinical responses are accompanied by the induction of strong CD4 + and CD8 + T cell immunity against the vaccine antigens. The antigen-specific cytotoxic T-cell responses in some responders reach magnitudes typically reported for adoptive T-cell therapy, and are durable. Our findings indicate that RNA-LPX vaccination is a potent immunotherapy in patients with CPI-experienced melanoma, and suggest the general utility of non-mutant shared tumour antigens as targets for cancer vaccination. Results of an exploratory interim analysis from a phase I trial show that an RNA vaccine targeted towards four melanoma-associated antigens produces durable objective responses in patients with melanoma that are accompanied by strong CD4 + and CD8 + T-cell immunity.